Ameliorating Effect of Gemigliptin on Renal Injury in Murine Adriamycin-Induced Nephropathy. (23rd February 2017) - Kim, Da Rae; Lee, Shin Yeong; Kim, Jin Sug; Kim, Yang Gyun; Moon, Ju-Young; Lee, Sang Ho; Lee, Tae Won; Ihm, Chun Gyoo; Jeong, Kyung Hwan
Abstract : Background . Previous studies have shown the antiapoptotic and anti-inflammatory potential of DPP-IV inhibitor in experimental models of renal injury. We tested whether DPP-IV inhibitor (gemigliptin) ameliorates renal injury by suppressing apoptosis, inflammation, and oxidative stress in mice with adriamycin nephropathy. Methods . Mice were treated with normal saline (control), gemigliptin (GM), adriamycin (ADR), or adriamycin combined with gemigliptin (ADR+GM). Apoptosis, inflammation, and oxidative stress were analyzed via western blotting, real-time PCR, light microscopy, and immunofluorescence. Results . In the ADR+GM group, urine albumin creatinine ratio decreased significantly compared with that in the ADR group on day 15. Glomerulosclerosis index and tubulointerstitial injury index in mice with adriamycin-induced nephropathy decreased after gemigliptin treatment. ADR group showed higher levels of apoptosis, inflammation, and oxidative stress-related molecules compared with the control group. The upregulation of these molecules was significantly reduced by gemigliptin. In the ADR group, the staining intensities of WT-1 and nephrin reduced, but these changes were ameliorated in the ADR+GM group. Conclusion . We demonstrated that gemigliptin ameliorates nephropathy by suppressing apoptosis, inflammation, and oxidative stress in mice administered adriamycin. Our data demonstrate that gemigliptin has renoprotective effects on adriamycin-induced nephropathy.